Effects of Long-term Professional Development Training in Technology Integration on Teacher and Student Performance - Heidi C. Blair; Howard Sullivan (Universitas Nurul Jadid Probolinggo, Indonesia, 2022)
The four primary questions addressed by the evaluation were: 1) Does the AZCOTT program influence the frequency of digital technology activities that teachers use with their students and that students perform in the classroom? 2) Does the program influence student performance of computer skills? 3) Does the program influence student self-reports of their technology skills? and 4) Does the program influence student self-reports of their use of technology for classroom activities? Also, investigated were the students’ ability to select appropriate software tools for given tasks and teacher attitudes toward the AZCOTT program.